Congenital imprinting disorders: Application of multilocus and high throughput methods to decipher new pathomechanisms and improve their management. Issue 5 (October 2015) - Soellner, Lukas; Monk, David; Rezwan, Faisal I.; Begemann, Matthias; Mackay, Deborah; Eggermann, Thomas
Abstract: Imprinting disorders (IDs) are a group of congenital diseases affecting growth, development and metabolism. They are caused by changes in the allele-specific regulation ("epigenetic mutation") or in the genomic sequence ("genetic mutation") of imprinted genes. Currently molecular tests in ID patients are generally restricted to single loci classically associated with the disease, but this approach limits diagnostic yield, because of the molecular and clinical heterogeneity between IDs. From the technical point of view, these limitations are aggravated by the lack of standardization in testing methodology, in the DNA sequences tested, and in clinical inclusion criteria prompting testing. However, an increasing number of new studies show that these problems can be addressed by the use of new tests targeting multiple loci and/or a total exome and genome analysis. The rapid development of efficient and high-throughput molecular techniques and their applications in research and diagnostics in the last decade have led to an impressive increase of knowledge on IDs and their basic pathomechanisms. In combination with the improvement of data recording and documentation, the diagnostic strategies are increasingly based on standardized protocols, and thereby provide the backbone for directed counseling, more personalized management, and new therapeutic approaches. Highlights: Imprinting disorders (IDs): congenital diseases affecting growth, development and metabolism. IDs are caused by epigenetic mutation or genetic mutation of imprinted genes. Single locus tests restrict diagnostic yield. Efficient and high-throughput molecular techniques lead to an impressive increase of knowledge on IDs and their pathomechanisms. The diagnostic strategies will be based on standardized protocols.